The incidence of the Constitutional Court in the work of the Judiciary and some ideas to face some eventual excesses produced in this context - Espinosa-Saldaña Barrera, Eloy (2007)
It became necessary to establish firm and solid institutional positions, that are respectful of the constitutional and legal current parameters. To know which is the position of the Judicial Power in certain matters, to let know that in front of the present bond, on which the Constitutional Court has been talking about, it must exist a real vocation to establish basic consensuses and generate a good coordination for one better integration, to formulate proposals and reforms, same in constitutional as legislative level for our country. Following this path, the Judicial Power must settle a position on certain matters in special of the constitutional procedural law, in order to them to addressed and resolved opportunely by the competent organs.